2009
DOI: 10.3200/joer.102.3.187-202
|View full text |Cite
|
Sign up to set email alerts
|

Word Problem-Solving Instruction in Inclusive Third-Grade Mathematics Classrooms

Abstract: The authors examined the effectiveness of strategy instruction taught by general educators in mixedability classrooms. Specifically, the authors compared the mathematical word problem-solving performance and computational skills of students who received schema-based instruction (SBI) with students who received general strategy instruction (GSI). Participants were 60 3rd-grade student participants randomly assigned to treatment conditions. Teachers pretested and posttested participants with mathematical problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 54 publications
2
62
0
5
Order By: Relevance
“…Retention data demonstrated that the participants retained the acquired skills 1, 3, and 5 weeks after the application was over. The acquisition and retention findings of this study were consistent with other study findings (Baki, 2014;Griffin & Jitendra, 2009;Jitendra et al, 2009;Jitendra et al, 2010;Karabulut et al, 2013;Kot, 2014;Na, 2009;Rockwell, 2012;Rockwell et al, 2011;Tuncer, 2009;Xin, 2008). Since no participant was able to generalize the stimulus at the posttest generalization session based on the generalization findings, generalization instruction was conducted.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Retention data demonstrated that the participants retained the acquired skills 1, 3, and 5 weeks after the application was over. The acquisition and retention findings of this study were consistent with other study findings (Baki, 2014;Griffin & Jitendra, 2009;Jitendra et al, 2009;Jitendra et al, 2010;Karabulut et al, 2013;Kot, 2014;Na, 2009;Rockwell, 2012;Rockwell et al, 2011;Tuncer, 2009;Xin, 2008). Since no participant was able to generalize the stimulus at the posttest generalization session based on the generalization findings, generalization instruction was conducted.…”
Section: Discussionsupporting
confidence: 82%
“…Studies in the existing literature report that the schema approach is effective in teaching verbal mathematics problems to typically developing individuals (Griffin & Jitendra, 2009;Jitendra et al, 2009) as well as those with learning disabilities (Griffin & Jitendra, 2009;Jitendra, DiPipi, & Perron-Jones, 2002;Jitendra & Hoff, 1996;Jitendra, Hoff, & Beck,1999;Jitendra et al, 2007;Na, 2009;Xin, 2008;Xin, Jitendra, & Deatline-Buchman, 2005), emotional and behavioral disorders (Jitendra, George, Sood, & Price, 2010), visual impairment (Tuncer, 2009), and intellectual disorders (Baki, 2014;Jitendra et al, 1998;Karabulut, Yıkmış, Özak, & Karabulut, 2013;Kot, 2014). However, only a limited number of studies have been conducted with individuals with ASD (Rockwell, 2012;Rockwell, Griffin, & Jones, 2011).…”
mentioning
confidence: 99%
“…Schematic representations that can be used to interpret and elaborate on information in the problem lead to enhanced problem solving performance (Pape & Tchoshanov, 2001). Such representations are essential components of many studies of SBI (e.g., Fuchs et al, 2009;Fuchs, Seethaler, et al, 2008;Fuson & Willis, 1989;Griffin & Jitendra, 2008;Jitendra et al, 2009;Jitendra, DiPipi, & Perron-Jones, 2002;Jitendra, Griffin, Deatline-Buchman, & Sczesniak, 2007;Jitendra, Griffin, McGoey, Gardill, Bhat, & Riley, 1998;Jitendra & Hoff, 1996;Jitendra, Hoff, & Beck, 1999;Lewis, 1989;Willis & Fuson, 1988;Xin, 2008;Xin, Jitendra, & Deatline-Buchman, 2005;Xin & SCHEMA-BASED INSTRUCTION 5 Zhang, 2009;Xin, Wiles, & Lin, 2008;Zawaiza & Gerber, 1993). For example, Fuchs, Seethaler, et al (2008) explored the effects of SBI for third graders identified as having mathematics and reading difficulties.…”
Section: Research On Schema-based Instruction and Problem Solvingmentioning
confidence: 99%
“…In order to effectively use vernacular languages for instruction at universities, it would be critical to have teachers who have both a good command of the particular vernacular language (either as their mother tongue or as a learned second language) as well as adequate knowledge of their subjects of specialisation. In addition, enhancement of a student's performance may require implementation of various complementary strategies, such as schema-based word-problem solving instructions 18,19 and peer-assisted inclusive instructions, 20,21 whenever applicable. Thus proficiency in the language of instruction and content knowledge should be complemented with other supportive and appropriate strategies.…”
Section: Performance Of Studentsmentioning
confidence: 99%
“…It is a widely accepted fact that language was, and may still be, a barrier to access to education of high quality in some developing countries. Proficiency in the language of instruction can affect comprehension of content and hence the performance of students in various subjects such as Mathematics [5][6][7] and Science. Hence the success of students whose mother tongue is not English or French may be compromised when they embark on university education at universities at which English or French is the language of instruction.…”
Section: Introductionmentioning
confidence: 99%